Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

In a textbook, I read the following:

We have already run into several examples of presentations. For instance, the free group $F(A)$ is presented by $(A\mid\emptyset)$ [ . . . ] $S_3$ as a quotient of the free group $F(\{x,y\})$ by the smallest normal subgroup containing $x^2, y^3$ and $yx = xy^2$: $(x,y\mid x^2,y^3,xyxy)$ in shorthand.

I am unsure why the condition $yx = xy^2$ is represented as $xyxy$ in the presentation? I need to transform it to an equation of the form $xyxy = 1$. But I don't succed, for example if I use the facts $x = x^{-1}$ and $y^{-1} = y^2$ which follow from $x^2 = 1$ and $y^3 = 1$ and substituting I got $yx = x^{-1}y^{-1}$. Now multiplying by $y$ and $x$ from the right yields $yxyx = 1$, but this is in general different from $xyxy = 1$, so why should it be the same?

share|improve this question
    
$xyxy=1$ is equivalent to $yxyx=1$. Multiply both sides of $xyxy=1$ on the left by $x^{-1}$, then multiply both sides on the right by $x$. –  Ted Feb 18 '13 at 2:18
add comment

1 Answer 1

You are on the right track, you just have to multiply by $x$ on the left and by $y$ on the right.

You correctly took into account that $x=x^{-1}$ and $y^2=y^{-1}$. Hence $yx=xy^2$ if and only if $xyx=y^{-1}$ if and only if $xyxy=1$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.